Exploiting photoredox catalysis for the synthesis of tetra- and di-hydrofurans. Issue 20 (13th May 2015) - Fumagalli, Gabriele; Boyd, Scott; Greaney, Michael F.
Graphical abstract: Abstract: Tetra- and di-hydrofuran heterocycles can be synthesised in a single step through the addition of functionalised alkyl bromides to styrene derivatives under photoredox catalysis.